Evaluating the effect of biochar rate and combination with fertilizer on the dynamics of soil nitrogen supply in tea plantation - Bangwei Zhang; Cenwei Liu; Qiang Li; Jing Ye; Yi Lin; Yixiang Wang; David L. Burton (Scientific Reports)
Abstract Tea plantations commonly receive substantial quantities of nitrogen (N) fertilizer, with potential for considerable N loss to occur. This study assessed N retention in acidic tea plantation soil and examined how different biochar application rates and fertilizer combinations affect N dynamics, highlighting the importance of innovative technologies to monitor and enhance N supply management. This research adopted a modified 2-week aerobic incubation and ion-exchange membrane (IEM) techniques to evaluate the soil N supply in tea plantations following early-summer top-dressing as influenced by various biochar rates and fertilizer combinations. We quantified the amount of mineralized N in acidic tea plantation soils during the summer. Our results show that biochar enhances soil N supply not by increasing N mineralization directly but by improving soil mineral N retention. Notably, a threshold effect was identified at biochar application rates of 20–30 tonnes ha−1. The window for maximizing the effectiveness of inorganic fertilizers applied during the summer months in tea plantations could only be 2–4 weeks. The use of biochar-based organic fertilizers can enhance this period by enhancing N retention and availability in the soil. Measuring N mineralization potential via aerobic incubations and N exposure using IEM technology effectively elucidated soil N dynamics during summer period.